Hadith #2551 - Sunan Abi Dawud - Abbad bin Tameem Mazni; Abdullah bin Abi Bakr bin Muh. b. 'Amr عبد الله بن أبي بكر بن محمد بن عمرو; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
When we alighted at a station (for stay), we did not pray until we united the saddles of the camels.
Grade: Sahih

Hadith #4864 - Sunan Abi Dawud - Abbad bin Tameem Mazni; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
I saw the Messenger of Allah(ﷺ). I asked: How did you see him? He said: He was white, good-looking, and when he walked, it looked as if he was descending to a low ground.
Grade: Sahih